2020
DOI: 10.3389/fvets.2020.569737
|View full text |Cite
|
Sign up to set email alerts
|

Roles of MOV10 in Animal RNA Virus Infection

Abstract: Animal epidemic diseases caused by RNA viruses are the primary threat to the livestock industry, and understanding the mechanisms of RNA virus clearance from target cells is critical to establish an effective method to reduce economic losses. As an SF-1, ATP-dependent RNA helicase in the UPF1p family, MOV10 participates in the RNA degradation of multiple viruses mediated via miRNA pathways and therefore contributes to a decrease in the replication of RNA viruses. This review primarily focuses on the bioactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…MOV10 and MOV10L1, belonging to SF1 RNA helicases, are implicated in diverse biological processes [ 1 , 8 , 20 ]. MOV10 and MOV10L1 homologs have been identified in human, mouse, frog and fly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MOV10 and MOV10L1, belonging to SF1 RNA helicases, are implicated in diverse biological processes [ 1 , 8 , 20 ]. MOV10 and MOV10L1 homologs have been identified in human, mouse, frog and fly.…”
Section: Discussionmentioning
confidence: 99%
“…Mov10L1 displays a specific expression in germ cell and has a key regulatory role in piRNA biogenesis [ 21 , 23 , 24 , 31 ]. Contrarily, MOV10 shows diverse expression pattern and versatile roles [ 1 , 8 , 9 , 10 , 20 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploring the SHFL interactome further, Balinsky and colleagues lastly confirmed the co-localization of SHFL with MOV10 in DENV infected cells, both of which re-localize to the DENV replication complex to restrict DENV replication. Importantly, several studies have previously shown that MOV10, a known P-body constituent, is itself an ISG with several anti-viral functions (reviewed in [88]). This represents one of the first studies to demonstrate a direct relationship between the anti-viral function of SHFL and phase-separated RNA granules, providing a novel link between the innate immune response to viral infection and RNP granule dynamics.…”
Section: Shiftless and Rna Granules During Rna Virus Infectionmentioning
confidence: 99%
“…Importantly, MOV10, one of the top MS hits, was found to be co-localized with SHFL at the viral-NS3-positive area in the perinuclear region of the DENV-infected cell, indicating that SHLF and MOV10 associate with the viral replication complex [ 22 , 32 ]. MOV10 is an ATP-dependent RNA helicase, which is reported to participate in cellular antiviral defense by regulating microRNA expression and mRNA stability [ 33 ]. Interestingly, in uninfected cells, the co-localization of SHFL and MOV10 was observed in the processing (P) body, which is a cytoplasmic granule involved in mRNA decay and translational suppression [ 34 ].…”
Section: Molecular Aspects Of Shfl In the Inhibition Of Flavivirusesmentioning
confidence: 99%